Development and validation of a secondary school classroom engagement instrument in math and science in the Ethiopian context - Berhanu, Alemayehu; Semela, Tesfaye; Moges, Belay (Frontiers in Psychology, 2025)
IntroductionClassroom engagement is the most influential variable in predicting students’ academic achievement. However, a valid and reliable instrument for measuring students’ classroom engagement in the Ethiopian context remains unexplored. This study aimed to develop and validate an Ethiopian secondary school student classroom engagement instrument.MethodA total of 119 items were selected through a rigorous literature review, and 40 of these items were initially drafted on the basis of expert judgment. These selected items were subsequently tested on 1,771 students: 383 for exploratory factor analysis (EFA), 1,346 for confirmatory factor analysis (CFA), and 42 for test–retest reliability. The internal consistency of the full scale and subscales of this tool were computed via Cronbach’s alpha. The measurements of invariance across gender and grade levels were analyzed to determine the level of equivalence of the instrument.ResultsThe findings revealed that this tool is valid and reliable and measures six sub-constructs of the attribute of classroom engagement. Therefore, the use of such valid and reliable tools in future measurement studies of Ethiopian high school students’ mathematics and science classroom engagement is suggested.ConclusionFinally, scholars in math and science research would benefit from using this tool either to cross-validate or synthesize their studies.